The effect of nonequilibrium structure state on the creep and superplastic behaviour of materials - Myshlyaev, M.M. (Физика и техника высоких давлений, 2003)
Mechanical behaviour at creep and superplasticity of large-grain and monocrystalline aluminum under torsion, large-grain molybdenum, fine-grain zinc alloy and amorphous cobalt alloy under tension are discussed from unified positions. It is shown that realization of their superplasticity requires fulfilment of structure-kinetic principle.